Seven new species of the leafhopper genus Tambocerus (Hemiptera: Cicadellidae) from the Indian subcontinent - Viraktamath, C. A. (Zootaxa, 2012)
Seven new species of the genus Tambocerus Zhang & Webb, Tambocerus acutus sp. nov., T. cholas sp. nov. (both from India:Tamil Nadu), T. daii sp. nov. (India: Kerala), T. furcostylus sp. nov. (India: Karnataka, Tamil Nadu), T. krameri sp. nov. (India,Karnataka; Sri Lanka), T. nilgiris sp. nov. (India: Tamil Nadu) and T. zahniseri sp. nov (India: Karnataka) are described andillustrated. T. viraktamathi Rao is redescribed and illustrated. A key to species of Tambocerus from the Indian subcontinent is also given.